Analysis of antimicrobial activity by defense fluid of Odontotermes Sarawakensis Holmgren on selected soil microbes - Almazani, Norshafiqah (2020)
This study was about using the agar disk diffusion assay to test the antimicrobial activity of methanol extract of defense fluid of termite soldier of Odontotermes Sarawakensis Holmgren. The antimicrobial test was done on two different types of mound soil microbes, Pkh.Umk_01 as Gram positive and Plch.Unik_02 as Gram negative. The termite soldiers were collected and its defense fluid was extracted with methanol that prepared at different concentration. Distilled water was served as negative control while the 6 nun of 10 mg/ml Gentamicin disk was served as positive control. Six crude extract concentration was used to determine the Minimum Inhibitory Concentration (MIC), which 10.0 mg/ml, 4.0 mg/ml, 2.0 mg/ml, 1.0 mg/ml, 0.5 mg/ml, and 0.1 mg/ml. From results, the MIC for both microbes was at different concentration, where the Pkh.Unik01 was at 0.5 mg/ml while the MIC of Pkh.Umk_02 was at the lowest concentration of 0.1 mg/ml. The antimicrobial activity were analyzed by using one way analysis of variance (ANOVA) with Independent t-test to perform a confident level of 95%. From ANOVA test, the results showed that not all concentration of defense fluid were significant as P<0.05 after performed the multiple comparison. There were only at concentrations of 10.0 mg/ml and 0.1 mg/ml that showed the significance as P<0.05. So, these concentrations possibly have a difference ability in antimicrobial activity with another concentrations. The control of 10 mg/ml of Gentamicin and 10 mg/ml of crude extract were significance as P<0.05 at Pkh.Umk_02 (Gram negative) and B. subtilis which it showed the differences in performance of antimicrobial activity in inhibiting microbes growth. In conclusion, it showed that the defense fluid extract of 0. sarawakensis was effective to inhibit the Gram negative of mound soil microbes.